2020
DOI: 10.1002/adom.202001378
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Disordered Colloidal Thin Films with Duplex Optical Elements for Advanced Anti‐Counterfeiting Coding

Abstract: Multiscale structures are found in nature to impart brilliant structural colors with integrated properties of multiple optical elements. However, it remains challenging to build more than one optical element into artificial photonic materials in practical manufacturing. Here, hierarchical disordered photonic superstructures (HDPSs) with optical properties arising from tailored interplay of thin‐film interference (TFI) and coherent scattering from amorphous colloidal arrays (ACAs) are fabricated through the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Duan and co-workers fabricated the thin-film APCs which were assembled by spherical/polyhedral metal-organic framework (MOF) colloidal particles. 101,102 Similarly, Chen et al reported a crack-free, arbitrarily bendable film of APCs with bright structural color prepared by vacuum filtration of colloidal suspension through an reduced graphene oxide-sulfopropyl methacrylate potassium salt (rGO-SPM) substrate (Fig. 3b and c).…”
Section: Infiltration-induced Colloidal Assemblymentioning
confidence: 95%
See 1 more Smart Citation
“…Duan and co-workers fabricated the thin-film APCs which were assembled by spherical/polyhedral metal-organic framework (MOF) colloidal particles. 101,102 Similarly, Chen et al reported a crack-free, arbitrarily bendable film of APCs with bright structural color prepared by vacuum filtration of colloidal suspension through an reduced graphene oxide-sulfopropyl methacrylate potassium salt (rGO-SPM) substrate (Fig. 3b and c).…”
Section: Infiltration-induced Colloidal Assemblymentioning
confidence: 95%
“…13g). 102 Non-iridescent structural colors displays in natural light, with bright mixed colors and special reflection under specular lighting. 102 Eu particles are easy to assemble into APCs with non-iridescent structural colors due to their instability and high polydispersity.…”
Section: Displaysmentioning
confidence: 99%
“…[15][16][17] Among them, fluorescent anticounterfeiting technology based on rare earth doped materials has been extensively used due to its cheaper cost, good concealment, not being easy to copy, convenient detection, and low toxicity. [18][19][20][21] For example, the Er:Cs 3 YbF 6 :Yb/Er@glass will emit light of different colors under the excitation of a 980 nm laser. 22 However, the use of different excitation for multimode anticounterfeiting has more significance.…”
Section: Introductionmentioning
confidence: 99%
“…— 14 In order to combat the severe problem of counterfeit and shoddy products, there are currently many anticounterfeiting technologies, such as digital anticounterfeiting technology, quick response code anticounterfeiting technology, radio frequency identification technology, and so forth 15–17 . Among them, fluorescent anticounterfeiting technology based on rare earth doped materials has been extensively used due to its cheaper cost, good concealment, not being easy to copy, convenient detection, and low toxicity 18–21 . For example, the Er:Cs 3 YbF 6 :Yb/Er@glass will emit light of different colors under the excitation of a 980 nm laser 22 .…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still some defects in practical application for these methods, such as complex instruments, slow assembly process, harsh assembly conditions, or unsuitable for magnified production. Inspired by the idea of rapid removal of solvent as mentioned above, infiltration-driven colloidal assembly method uses porous paper material as the medium, which can rapidly absorb the solvent in the colloidal dispersion (within milliseconds), thereby quickly fixing the colloidal particles on the paper surface to form an ACA. Because of its rapid, simple, and flexible process, the infiltration-driven colloidal assembly method is extremely suitable for the large-scale preparation of ACA and for easy to design various patterns.…”
mentioning
confidence: 99%